Constraining stellar assembly and AGN feedback at the peak epoch of star formation - Kimm, T; Kaviraj, S; Devriendt, J; Cohen, S; Windhorst, R; Dubois, Y; Slyz, A; Hathi, N; Jr, R; O'Connell, R; Dopita, M; Silk, J (Oxford University Press, 2012)

(untitled)
We study stellar assembly and feedback from active galactic nuclei (AGN) around the epoch of peak star formation (1 ≲ z ≲ 2), by comparing hydrodynamic simulations to rest-frame UV-optical galaxy colours from the Wide Field Camera 3 (WFC3) Early Release Science (ERS) programme. Our adaptive mesh refinement simulations include metal-dependent radiative cooling, star formation, kinetic outflows due to supernova explosions and feedback from supermassive black holes. Our model assumes that when gas accretes on to black holes, a fraction of the energy is used to form either thermal winds or subrelativistic momentum-imparting collimated jets, depending on the accretion rate. We find that the predicted rest-frame UV-optical colours of galaxies in the model that includes AGN feedback are in broad agreement with the observed colours of the WFC3 ERS sample at 1 ≲ z ≲ 2. The predicted number of massive galaxies also matches well with observations in this redshift range. However, the massive galaxies are predicted to show higher levels of residual star formation activity than the observational estimates, suggesting the need for further suppression of star formation without significantly altering the stellar mass function. We discuss possible improvements, involving faster stellar assembly through enhanced star formation during galaxy mergers while star formation at the peak epoch is still modulated by the AGN feedback.